Engineered exosomes for targeted co-delivery of miR-21 inhibitor and chemotherapeutics to reverse drug resistance in colon cancer - Liang, Gaofeng; Zhu, Yanliang; Ali, Doulathunnisa Jaffar; Tian, Tian; Xu, Huantian; Si, Ke; Sun, Bo; Chen, Baoan; Xiao, Zhongdang (Journal of nanobiotechnology, 2020)
Background 5-Fluorouracil (5-FU) has been commonly prescribed for patients with colorectal cancer (CRC), but resistance to 5-FU is one of the main reasons for failure in CRC. Recently, microRNAs (miRNAs) have been established as a means of reversing the dilemma by regulating signaling pathways involved in initiation and progression of CRC. However, how to safely and effectively deliver miRNA to target cells becomes a main challenge. Results In this study, Engineered exosomes were exploited to simultaneously deliver an anticancer drug 5-FU and miR-21 inhibitor oligonucleotide (miR-21i) to Her2 expressing cancer cells. Purified engineered exosomes from the donor cells loaded with 5-FU and miR-21i via electroporation to introduce into 5-FU-resistant colorectal cancer cell line HCT-116 5FR . Furthermore, systematic administration of 5-FU and miR-21i loaded exosomes in tumor bearing mice indicated a significantly anti-tumor effect. The results showed that the engineered exosome-based 5-FU and miR-21i co-delivery system could efficiently facilitate cellular uptake and significantly down-regulate miR-21 expression in 5-FU resistant HCT-116 5FR cell lines. Consequently, the down-regulation of miR-21 induced cell cycle arrest, reduced tumor proliferation, increased apoptosis and rescued PTEN and hMSH2 expressions, regulatory targets of miR-21. Of particular importance was the significant reduction in tumor growth in a mouse model of colon cancer with systematic administration of the targeting miR-21i. More excitedly, the combinational delivery of miR-21i and 5-FU with the engineered exosomes effectively reverse drug resistance and significantly enhanced the cytotoxicity in 5-FU-resistant colon cancer cells, compared with the single treatment with either miR-21i or 5-FU. Conclusion The strategy for co-delivering the functional small RNA and anticancer drug by exosomes foreshadows a potential approach to reverse the drug resistance in CRC and thus to enhance the efficacy of the cancer treatment.